2004
DOI: 10.1002/jez.a.104
|View full text |Cite
|
Sign up to set email alerts
|

Cross communication between signaling pathways: Juvenoid hormones modulate ecdysteroid activity in a crustacean

Abstract: Methyl farnesoate is a juvenoid hormone that regulates a variety of processes in crustaceans including male sex determination among daphnids (Branchiopoda, Cladocera). The synthetic juvenoids pyriproxyfen and fenoxycarb mimic the action of methyl farnesoate in daphnids. In the present study we tested the hypothesis that juvenoids also can regulate ecdysteroid activity in a crustacean (Daphnia magna). Methyl farnesoate, pyriproxyfen, and fenoxycarb all disrupted ecdysteroid-regulated aspects of embryo developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 25 publications
1
52
0
Order By: Relevance
“…It has been reported that Ec is responsible for embryo development, larval molts, pupation, and metamorphosis in Drosophila, Bombyx mori and other arthropods (Riddiford 1993, Subramoniam 2000, Sekimoto et al 2006. The Ec is known to regulate a number of biological processes by coordinating with juvenile hormone (JH; Dubrovsky 2005) and cross talk between them has been reported in Daphnia and other arthropods (Mu & LeBlanc 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Ec is responsible for embryo development, larval molts, pupation, and metamorphosis in Drosophila, Bombyx mori and other arthropods (Riddiford 1993, Subramoniam 2000, Sekimoto et al 2006. The Ec is known to regulate a number of biological processes by coordinating with juvenile hormone (JH; Dubrovsky 2005) and cross talk between them has been reported in Daphnia and other arthropods (Mu & LeBlanc 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other two xeno-ecdysteroids, strong fytoecdysterone agonist Ponasterone A and synthetic ecdysone agonist bisacylhydrazine RG-102240, are potent lignads for EcR (that heterodimerizes with RXR) in U. pugilator (Wu et al 2004). Xenobiotics can also affect EcR levels in target cells as was documented for synthetic juvenoids pyriproxifen and fenoxycarb that attenuated expression of mRNA encoding EcR (and its heterodimer partner USP) in the insect in vitro model with Drosophila Kc cells (Mu & LeBlanc 2004).…”
Section: Role Of Classical Endocrine Glands In Reproductionmentioning
confidence: 88%
“…Physiological and biochemical studies would be useful to uncover such systemic changes in metabolism in response to JHA treatment. Furthermore, alteration of chitin metabolism underscores connections between MF and ecdysis due to genetic crosstalk with ecdysone pathways (Mu and LeBlanc, 2004). Third, involvement of the rheb receptor in response to MF is, to our knowledge, a novel observation linking this protein to a crustacean hormonal response.…”
Section: Introductionmentioning
confidence: 87%
“…Third, as a classic example of phenotypic plasticity and epigenetic regulation, it offers the possibility of uncovering molecular mechanisms responsible for these ecologically and evolutionarily central mechanisms. Fourth, evidence indicates important couplings between juvenile hormone (JH) pathways and ecdysone pathways in Daphnia (Mu and LeBlanc, 2004), which are likely to be useful for genetic and genomic analyses of these pathways across the Ecdysozoa. Olmstead and LeBlanc (2002) were first to demonstrate production of male broods of D. magna in response to the sesquiterpenoid hormone methyl farnesoate (MF), the unepoxidated form of insect JH III.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation